AMERICAN SLANGS THAT ARE USED IN DAILY COMMUNICATION. THE BRITISH AND THE AMERICAN SLANGS THAT ARE USED IN THEIR DAILY COMMUNICATION. (Journal of Universal Science Research, 2025)
Slangs are one of the most key points of effective interaction in any language, particularly in the English language. Although the usage of slangs in communication is more complicated than we expected , learning its meaning is vital for us. Slangs often cannot be translated with their literal meaning as idioms, phrasal verbs , jargons